(untitled) (Literary Voice, 2023)
The present paper focuses on the panoptical narrative of the Doctrine of Discovery which has remained entrenched in the colonial discourse of Europeans in North America. The narrative of Doctrine, which has its roots in the early medieval period, has been used as a racist paradigm to violate the fundamental rights of the indigenous peoples. In the eighteenth century, the Doctrine became a legal document to assimilate and annex the lands of the First Nations in Canada. The Doctrine focused on assimilating the non-whites into the mainstream culture through their mythical fabrication. The symbolic misrepresentation of indigenous peoples in mainstream literary and cultural works has facilitated the oppression of the indigenous communities